ELP: Tractable Rules for OWL 2. - Krötzsch, M; Rudolph, S; Hitzler, P (Springer, 2008)
We introduce as a decidable fragment of the Semantic Web Rule Language (SWRL) that admits reasoning in polynomial time. is based on the tractable description logic , and encompasses an extended notion of the recently proposed DL rules for that logic. Thus extends with a number of features introduced by the forthcoming OWL 2, such as disjoint roles, local reflexivity, certain range restrictions, and the universal role. We present a reasoning algorithm based on a translation of to Datalog, and this translation also enables the seamless integration of DL-safe rules into . While reasoning with DL-safe rules as such is already highly intractable, we show that DL-safe rules based on the Description Logic Programming (DLP) fragment of OWL 2 can be admitted in without losing tractability. © 2008 Springer Berlin Heidelberg.